The concept, essence and tools of strategic accounting in commercial organizations - Sitenko, D.A.; Akhmetova, A.B. (KSU Publ., 2020)
In this article, the main theoretical features of strategic accounting are studied, the features of this concept are considered, and they also familiarized themselves with the scope of application, as well as with situations in which this type of accounting is best applied. Basically, many organizations rely on strategic accounting methods, which are one of the sections of management accounting. This type of accounting and provides all the necessary information to managers of the enterprise about possible scenarios of the organization, taking into account the expected implemented operations for innovative development, i.e. assessment of the forecast value of the innovation potential, and information support of the leadership in the field of strategic decisions regarding the innovative development of the enterprise. At the moment, the question of introducing a strategic approach to management accounting, which represents the highest level of the accounting and analytical system of the enterprise, is becoming particularly relevant. The development of the forecasting function of management accounting involves the formation of a system for collecting, grouping, and processing data on the company's revenues and expenditures in the context of individual business segments, projects, and activities. This requires the identification of new cost accounting facilities and strategic responsibility centers, restructuring of the enterprise management system, the choice of strategic accounting methods, the use of tools such as strategic budgeting, a system of targeted balance indicators, etc.
Keywords: strategic accounting; strategic information; planning; enterprise structure; costs; nonfinancial indicators; accounting methods